ANALISIS KORELASI ANTARA ETOS KERJA DENGAN PRESTASI KERJA PEGAWAI (Studi Pada Bagian Hukum Sekretariat Daerah Kabupaten Kutai Barat) - Sabet, Eli (PREDIKSI, 2016)
This study aims to know the Work Ethic, and the correlation between Job Performance with Job Performance Work Ethics Officer Legal Division of the Secretariat of West Kutai. The results showed that the empirical rs amounted to 0.521 greater than the theoretical rs of 0.423 for n = 22, at a significance level of 5%. Thus it can be said that there is a significant relationship between the variables work ethic with variable performance. The results showed also that the obtained value of R Square of 0.271. This means that the contribution made by the work ethic variable to variable work performance was 27.1% and 71.9% were influenced by other variables not examined in this study. Thus it can be said that the hypothesis that the writer formulated in this study can be received and verified.